Kidney Transplantation: A Guide to the Care of Kidney Transplant Recipients - McKay, Dianne B.; McKay, Dianne B.; Steinberg, Steven M.; Steinberg, Steven M. (Springer US : Imprint: Springer, 2010)
Kidney Transplantation: A Guide to the Care of Kidney Transplant Recipients is an easy to read, up to date, clinical resource written by experts in the field of kidney transplantation. The book explains how donors and recipients are selected for transplantation, how the surgical procedure is performed, and how the experts recognize and treat rejection. This guide to the care of the kidney transplant recipient aims to provide practical guidelines for management of the post-transplant recipient and is targeted to community nephrologists and general internists who care for the patient with a kidney transplant. Dianne B. McKay, MD, is Associate Professor at The Scripps Research Institute, La Jolla, California. Steven M. Steinberg, MD, is affiliated with the Sharp Memorial Hospital, San Diego, California.